2012
DOI: 10.2478/v10007-012-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial rheology: An overview of measuring techniques and its role in dispersions and electrospinning

Abstract: Colloidal disperse systems represent the increasing number of modern delivery systems whose primary characteristic, a large interfacial area, causes thermodynamic instability. Therefore, the foremost challenge in dispersion design is the reduction of interface instability and an understanding of the behaviour of interfaces. Interfacial rheology is one of the most powerful tools for observing occurrences at the interphase. As previously mentioned, the stability of such systems is provided by the formation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 62 publications
(85 reference statements)
1
45
0
3
Order By: Relevance
“…Of the various loading possibilities, physical entrapment is currently the most widespread, since the drug in the nanofibers is protected against unfavorable environmental conditions and it offers good control over the drug release (8). Moreover, incorporation of a drug in nanofibers is relatively easy to perform, since the drug is simply dissolved in the polymer solution prior to electrospinning and the formation of an amorphous drug is favoured due to a very limited time being available for drug recrystallization during the fiber formation (9,11). A typical release profile from such nanofibers exhibits an initial burst effect followed by an almost linear, sustained release (1,5).…”
Section: Nanofibers As Progressive Dressings For Chronic Wound Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Of the various loading possibilities, physical entrapment is currently the most widespread, since the drug in the nanofibers is protected against unfavorable environmental conditions and it offers good control over the drug release (8). Moreover, incorporation of a drug in nanofibers is relatively easy to perform, since the drug is simply dissolved in the polymer solution prior to electrospinning and the formation of an amorphous drug is favoured due to a very limited time being available for drug recrystallization during the fiber formation (9,11). A typical release profile from such nanofibers exhibits an initial burst effect followed by an almost linear, sustained release (1,5).…”
Section: Nanofibers As Progressive Dressings For Chronic Wound Therapymentioning
confidence: 99%
“…Although various methods, such as self-assembly, phase separation or electrospinning, can be used for their preparation, only the electrospinning technology, which uses high voltage supply to transform a polymer solution into solid nanofibers, is versatile, efficient, widely used and applicative on the industrial scale ( Fig. 3) (10,11).…”
Section: Use Of Nanofibers In the Biomedical Fieldmentioning
confidence: 99%
“…Rošic 23 et al reported that the interfacial rheological parameters were determined by polymer concentration, directly affect jet initiation and diameter reducing. Pelipenko 24 et al showed that the interfacial rheological characteristics were relevant in systems with large interfacial areas, which help to decrease the jet diameter and format nanofiber. Since the shorter spinneret to collector distance, EDW charged jet has less relax time to be elongated and refined.…”
Section: Introductionmentioning
confidence: 99%
“…As caraterísticas viscoelásticas do bulk e da interface podem ser avaliadas por meio de vários procedimentos experimentais, dos quais podem se destacar os experimentos de relaxação da tensão, relaxação da deformação e/ou medidas oscilatórias (Pelipenko et al, 2012). Os experimentos oscilatórios permitem avaliar a resposta de fluidos complexos na região viscoelástica linear através da aplicação de um cisalhamento oscilatório de amplitude baixa.…”
Section: âNgulo De Contatounclassified
“…Neste tipo de medidas, os métodos mais comumente usados são os métodos diretos de rotação em reômetros com geometria cilíndrica concêntrica ou com geometria de cone e placa (PELIPENKO et al, 2012). Neste trabalho, foi utilizado um reômetro HAAKE MARS (Thermo Scientific) com geometria de cone e placa como mostrado na figura 18 para determinar os módulos elástico e viscoso do bulk da solução aquosa de tensioativo.…”
Section: âNgulo De Contatounclassified